'Don't Play a Lone Hand': A century of leadership in American art education, 1840–1940. Issue 3 (1st September 2014) - Stankiewicz, Mary Ann
Knowledge of the field and visions for the future are vital for transformational leadership in art education, according to current scholars. With the development of common schools and hierarchical bureaucracies in Massachusetts, in a context of belief in artistic genius, early historians of art education told stories of heroes and experts. During the 1870s, Walter Smith (1836–1886) lectured students at Massachusetts Normal Art School that great men demonstrated commitment to work, indomitable courage and persistence in their heroic leadership. In the mid-1890s, Massachusetts' agent for industrial drawing Henry Turner Bailey (1865–1931) categorized art supervisors as geometric solids: sphere, cube and cylinder. About a decade later, Bailey called for a servant model of leadership, with traits that can be interpreted as stereotypically feminine. Networked leadership emerged in the early twentieth century as administrative progressives worked together to construct a business of art education with engaged stakeholders, distributed leadership and a rationale emphasizing functions of visual arts in everyday life. Royal Bailey Farnum (1884–1967) served as central node for most of the overlapping leadership networks. As Executive Vice President of Rhode Island School of Design during the 1930s and 1940s, he introduced strategic planning that prepared the School for post-war success. Leadership in American art education has changed in response to cultural contexts, social factors, institutional demands, and male and female performances of power. How will art educators play the leadership game in the years to come?